KAJIAN SOSIOLINGUISTIK MASYARAKAT TRANSMIGRAN DI RIAU DAN RELEVANSINYA TERHADAP PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA ARAB - ABDAL CHAQIL HARIMI (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2022)
This Research explains about Used language in Sari galuh VillageSociety. Researcher uses descriptive qualitative research with observation method,interview method, and documentation method. Results of this research are first,There is Multilanguage. Because, a lot of people came in Sari galuh Village forTransmigration program. They were from Medan, Java, Bukittinggi, and theoriginal people in Riau. The multilanguage process is caused transmigrationprogram or migration in Sociolinguistic. The second result shows that Javaneseand bahasa are most dominant languages in Sari Galuh village. Third, there isinfluenced environment for language process in Sari Galuh Village. Thesuccessfully in speaking learning skills can be approved with making arabicdomination dan arabic environment in the class.